POSTHUMANISM: HISTORY, GOALS AND IMMINENT PERILS - Gajic, Aleksandar; Despotović, Ljubiša (Serbian political thought, 2024)
The Paper studies the origin, development, main representatives, and basic characteristics of the posthumanist movement, its normative positions and goals (including its relation towards technology and nature), as well as the similarities and differences between modern posthumanism and transhumanism. In order to compare the posthumanist movement with humanistic modernism and notice their basic similarities and differences, which are crucial for understanding the relationship of man and technology towards natural conditions, the second part of the Paper points out the basic characteristics of modern humanistic anthropocentrism and its attitude towards technique. The final part of the Paper concerns the critique of posthumanism from the perspective of Christian personalism, which opens up possibilities for us to have a different view of the problems of postmodern living that posthumanism wants to overcome.
Keywords: posthumanism; Anthropocene; Christianity; humanism; modernity; posthumanism technique/technology